Customer Experience in Marketing Research: a state-of-the-art Literature Review - Lazaare Ghita; Ghannam-Zaim Ouaffa (African Scientific Journal, 2023)
Customer experience has become a central research theme within the field of marketing. This study presents a comprehensive and chronological exploration of the concept of customer experience, tracing its evolution from its emergence in the 80s to its latest developments up to 2018. Through a meticulous analysis of the existing literature, this paper shows the evolution of the concept, the diverse angles under which it was examined, and the seminal contributions that shaped it. It studies the work of founding researchers who laid the groundwork for the study of customer experience in marketing in the early 1980s and 1990s, and then describes the different trajectories research has taken in regard to customer experience as the new millennium unfolded, particularly within the context of retail environments. It also highlights the turning point and increasing interest in the concept around the year 2007. Finally, the study navigates the currents of recent scholars in the last decade, as customer experience has gained more importance in the service industry. This paper exposes the different definitions, dimensions and theoretical underpinnings under which the concept has been examined. It presents the converging and contrasting perspectives of the authors and existing frameworks that can be used when undertaking research involving customer experience. Furthermore, the main findings and interpretations are summarized, and a clear demarcation between the concept of customer experience and adjacent concepts of service quality and satisfaction is proposed. In addition to elucidating the historical evolution of the concept, this paper provides a ground analysis researchers can build upon to undertake future research on customer experience.